Sosialisasi Perpajakan: Membangun Jembatan antara Kesadaran dan Pengetahuan Pajak Menuju Kepatuhan Pajak Bumi dan Bangunan - Ismau, Daymiliana Astrivani; Safriliana, Retna; Parawiyati, Parawiyati (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Data on the realization of Land and Building Tax revenue in Niukbaun Village has not met the target set by the Regional Revenue Agency Office of Kupang Regency from 2019 to 2022. This research aims to evaluate the role of tax socialization as a moderator of the relationship between tax awareness and knowledge and taxpayer compliance. In this research the author used a research design with a quantitative approach. The location of this research was carried out in Niukbaun Village, West Amarasi District, Kupang Regency, East Nusa Tenggara. Respondents in the research were all people who paid PBB in Niukbaun Village, West Amarasi District, Kupang Regency, totaling 1,373 taxpayers. Data processing uses SPSS. The research results show that the tax socialization variable moderates tax awareness on tax compliance and tax knowledge on tax compliance. The implications of this empirical evidence indicate that the tax socialization program carried out is able to encourage tax compliance so that this program can be implemented continuously.